The Location of Business Support Programs: Does the Knowledge Context Matter? - Haifeng Qian; Kingsley E. Haynes; Sidney C. Turner (European Regional Science Association (ERSA), 2010)
Business support programs, represented by business incubators (BIs) and small business development centers (SBDCs), play an important role in assisting new or small firms, nurturing entrepreneurial culture, and fostering regional economic growth. For that reason, the location of these programs may interest regional planners or economic practitioners who have the incentive to create or attract these programs. Our previous studies have found that the presence of both types of business support programs is positively associated with the level of agglomeration and negatively associated with the level of business development. It is however unclear whether the local knowledge context may influence the local presence of BIs or SBDCs. This paper examines the role of knowledge in shaping the geography of BIs and SBDCs in the US using county-level data. Human capital, the university, and high technology are used as the proxies for knowledge. Their effects on the presence of BIs and SBDCs are investigated in binomial logistic regressions. We also control other county-specific characteristics by including three common factors derived via factor analysis from 27 demographic, social, and economic variables. This study highlights business support programs as the link between regional innovation systems and small or new firms.
Keywords: 330